Scottish Missions to China : Commemorating the Legacy of James Legge (1815-1897) - Chow, Alexander, (Theology and Mission in World Christianity ;, 2022)
This volume explores the important legacy of Scottish missions to China, with a focus on the missionary-scholar and Protestant sinologist par excellence James Legge (1815-1897). It challenges the simplistic caricature of Protestant missionaries as Orientalizing imperialists, but also shows how the Chinese context and Chinese persons "converted" Scottish missionaries in their understandings of China and the broader world. Scottish Missions to China brings together essays by leading Chinese, European, and North American scholars in mission history, sinology, theology, cultural and literary studies, and psychology. It calls attention to how the historic enterprise of Scottish missions to China presents new insights into Scottish-Chinese and British-Chinese relations.